2013
DOI: 10.1590/s0034-70942013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Relevância de exames de rotina em pacientes de baixo risco submetidos a cirurgias de pequeno e médio porte

Abstract: Background and objectives: Preoperative tests aim to reduce morbidity and mortality of surgical patients, cost of perioperative care, and preoperative anxiety. Clinical evaluation allows defi ning the need for additional tests and strategies to reduce the surgical-anesthetic risk. The aim of this study was to evaluate the benefi t of routine preoperative testing of low-risk patients undergoing minor and medium surgical procedures. Methods: A descriptive cross-sectional study of 800 patients seen at the preanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…However, the medical literature has indicated that abnormalities found in POCEs are not usually clinically important, are generally ignored, do not contribute to changes in the anesthetic-surgical management and are not related to perioperative complications. In addition, there is a risk that non-clinically based tests, especially on the occurrence of false positives, may lead to further invasive investigations, leading to postponement of operations as well as inadequate treatment 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the medical literature has indicated that abnormalities found in POCEs are not usually clinically important, are generally ignored, do not contribute to changes in the anesthetic-surgical management and are not related to perioperative complications. In addition, there is a risk that non-clinically based tests, especially on the occurrence of false positives, may lead to further invasive investigations, leading to postponement of operations as well as inadequate treatment 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of MAP in the development of SSI was not a predominant factor in the researched scientific studies 7,[15][16][17] .…”
Section: Resultsmentioning
confidence: 99%
“…O conceito de vulnerabilidade é entendido como a probabilidade de uma população ser atingida por problemas, ameaças, ou danos à saúde. Tal suscetibilidade leva à necessidade de priorização da assistência a tais eventos, promovendo, assim, o princípio da equidade (25) . A equidade é definida como a oferta de maior atenção aos indivíduos que mais a necessitam, provendo a cada um as ações de saúde segundo as suas demandas, com o intuito de superar as desigualdades existentes.…”
Section: Discussionunclassified
“…A superação do desafio de responder às demandas dos usuários utilizando os recursos que se têm disponíveis depende da eficácia e otimização dos recursos financeiros e do desenvolvimento de uma relação custo-benefício positiva (25) . O acesso às ações e serviços de saúde permite a integralidade do cuidado, por meio do fluxo do usuário pela rede de atenção à saúde, garantindo a oferta de serviços de diferentes densidades tecnológicas de acordo com sua necessidade (27) .…”
Section: Discussionunclassified